The form and role of deviation in a collection of poems Mengapa Luka Tidak Memaafkan Pisau by M. Aan Mansyur - Munaris, Munaris; Prasetyo, Heru; Maharani, Salwa Pramesti; Takahashi, Tasuku (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2024)
The problem in this study is the form and role of deviation in the collection of poems Mengapa Luka Tidak Memaafkan Pisau by M. Aan Mansyur. This study aims to describe the form and role of deviation in the collection of poems Mengapa Luka Tidak Memaafkan Pisau by M. Aan Mansyur. The method used in this study is descriptive qualitative which uses a collection of poems Mengapa Luka Tidak Memaafkan Pisau by M. Aan Mansyur as a data source. There are 8 titles used as data sources to represent the entire poem. The data analysis technique in this research is text analysis. The steps taken by the author in carrying out data analysis include: 1) reading and observing carefully the collection of poems Mengapa Luka Tidak Memaafkan Pisau by M. Aan Mansyur, 2) collecting data, 3) reducing the data, 4) presenting the results of the analysis, and 5) draw conclusions. The results of the research show that poets use lexical deviation, phonological deviation, grammatical deviation, semantic deviation, graphological deviation, dialect deviation, register deviation, and historical deviation. The results of the study show that the form and role of deviation in the collection of poems Mengapa Luka Tidak Memaafkan Pisau by M. Aan Mansyur play a role in obtaining density of meaning, generating an atmosphere, looking for new expressions, actualizing ideas, obtaining aesthetic effects, achieving visual beauty, finding accuracy in pronunciation through regional characteristics, strengthening the atmosphere, and achieving accuracy of meaning.